Co-infection of high-risk Human papillomavirus and Human T-lymphotropic virus-1 among women living with HIV on antiretroviral therapy at a tertiary hospital in Kenya - Kangethe, James Mburu; Gichuhi, Stephen; Odari, Eddy Okoth; Pintye, Jillian; Mutai, Kenneth; Abdullahi, Leila; Maiyo, Alex; Mureithi, Marianne W. (Frontiers in Virology, 2023)
Globally, 15% of reported cancers are virus-associated. Cancer-causing viruses include highrisk Human papillomavirus (HR-HPV), the causative agent of cervical cancer, and Human Tlymphotropic virus type-1 (HTLV-1), the causative agent of adult T-cell leukemia (ATL).HTLV-1 infection may enhance susceptibility to acquiring HR-HPV infections due to its retrovirus properties, resulting in increased cervical abnormalities among women living with HIV (WLHIV). In Kenya, there is a paucity of data on the burden of HR-HPV/HTLV-1 coinfection among WLHIV. We determined the prevalence of HR-HPV and HTLV-1 coinfection among WLHIV on antiretroviral therapy (ART) at Kenya's national referral hospital, Kenyatta National Hospital (KNH).We conducted a cross-sectional study among WLHIV on ART attending KNH's HIV care clinic. Study nurses collected a cervical sample with a cytobrush for HPV genotyping using Gene Xpert ® assays and HPV Genotypes 14 Real-TM Quant. Peripheral blood mononuclear cells were used for HTLV-1 DNA detection. Differences in frequency distributions of characteristics between WLHIV with and without HR-HPV and HTLV-1 co-infections were assessed using the Chi-square tests.A total of 647 WLHIV enrolled in this study with a mean age of 42.8 years (SD 8.7); 93% were on ART for >1 year and 8.8% were not virally suppressed (>1000 HIV RNA copies/mL). The HTLV-1 positivity rate among WLHIV was 3.1% overall and 7.6% among those with HR-HPV. WLHIV with HR-HPV 31 had the highest proportion of HR-HPV/HTLV-1 co-infection (31.6%). In contrast, WLHIV with HR-HPV 39 had the lowest proportion of co-infection (7.1%). Participants with HR-HPV/HTLV-1 co-infections were older compared to those without the co-infections (35.2% vs. 23.3%). A higher proportion of women with HR-HPV/ HTLV-1 co-infections had their sex debut before the age of 18 years (p=0.012). Women coinfected with HR-HPV/ HTLV-1 were diagnosed with HIV at ≥ 35 years compared to those without infection (70.6% vs. 41.9%, p= 0.019).We found that HTLV-1 infection was more common among WLHIV on ART who also had HR-HPV and that co-infections were associated with the age of sexual debut and the age of HIV diagnosis.